2000
DOI: 10.3171/jns.2000.93.5.0845
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic tolerance in the rat neocortex following hypothermic preconditioning

Abstract: These findings indicate that hypothermic preconditioning induces a form of delayed tolerance to focal ischemic damage. The time course over which tolerance occurs and the ability of a protein synthesis inhibitor to block tolerance suggest that increased expression of one or more gene products is necessary to establish tissue tolerance following hypothermia. The attenuation of hypoxic injury in vitro following in vivo preconditioning indicates that tolerance is due, at least in part, to direct effects on the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 44 publications
2
59
2
1
Order By: Relevance
“…This would shorten the period of terminal depolarization and, thus, mitigate all pathologic processes triggered during the state of energy depletion and manifested after recovery from ischemia. However, transient hypothermia has been shown to induce rapid and delayed forms of tolerance to ischemic injury, suggesting that it can trigger an active process protecting cells from damage caused by ischemia (Nishio et al, 2000;Yunoki et al, 2002Yunoki et al, , 2003. The magnitude of tolerance induced by hypothermic preconditioning was found to be dependent on the depth of hypothermia with hypothermia set at 25.51C producing the most pronounced effects (Yunoki et al, 2002).…”
Section: Resultsmentioning
confidence: 87%
“…This would shorten the period of terminal depolarization and, thus, mitigate all pathologic processes triggered during the state of energy depletion and manifested after recovery from ischemia. However, transient hypothermia has been shown to induce rapid and delayed forms of tolerance to ischemic injury, suggesting that it can trigger an active process protecting cells from damage caused by ischemia (Nishio et al, 2000;Yunoki et al, 2002Yunoki et al, , 2003. The magnitude of tolerance induced by hypothermic preconditioning was found to be dependent on the depth of hypothermia with hypothermia set at 25.51C producing the most pronounced effects (Yunoki et al, 2002).…”
Section: Resultsmentioning
confidence: 87%
“…Regression analysis showed no correlation between the number of days spent in torpor immediately before euthanasia and sensitivity to 2 h OGD in hAGS (R 2 = 0.099, P = 0.13). The tolerance of ibeAGS to OGD may be because of the preconditioning effects of hypothermia experienced during previous hibernation bouts (Nishio et al, 2000). Hypothermic preconditioning has been reported to last less than 7 days in rats (Nishio et al, 2000); therefore, we tested hippocampal tissue collected from AGS during the summer months (July-August) that had not been torpid for at least 4 months and should no longer be affected by hypothermic preconditioning.…”
Section: Results Ibeags and Hags Survive Prolonged Ogdmentioning
confidence: 99%
“…The tolerance of ibeAGS to OGD may be because of the preconditioning effects of hypothermia experienced during previous hibernation bouts (Nishio et al, 2000). Hypothermic preconditioning has been reported to last less than 7 days in rats (Nishio et al, 2000); therefore, we tested hippocampal tissue collected from AGS during the summer months (July-August) that had not been torpid for at least 4 months and should no longer be affected by hypothermic preconditioning. We found that baseline cell death increased to 50.9% ± 5.8% (P < 0.001 versus ibeAGS or hAGS), but similar to the winter animals, there was no increase in cell death in response to 30 mins OGD ( Figure 1C), suggesting that tolerance to OGD is not because of preconditioning effects of recent low body temperatures.…”
Section: Results Ibeags and Hags Survive Prolonged Ogdmentioning
confidence: 99%
“…This suggests that EE, like other preconditioning stimuli (Barone et al 1998;Nishio et al 2000), requires new protein synthesis. The predominant effect of TNF-α is to alter gene expression (Abbas and Lichtman 2003).…”
Section: Adaptive Nature Of Activity-dependent Neuroprotectionmentioning
confidence: 99%